HOW TO BE A GOOD LANGUAGE TEACHER - Saadillah Saadillah (English Department of Faculty of Tarbiyah and Teacher Training, 2012)
AbstractThere are two crucial questions about the study of language teacher. The first question is “How is a good teacher?” The second question is “How is a good language teacher? To answer those questions, it should be understood that teacher is a usual creation of God. Like an English proverb says”there is no one perfect so, the teacher maybe will do the mistakes. The teacher maybe has some weakness . This writing tries describing some facts about teachers as general, and introducing the reader about how is going to be a good language teacher.